Genome-wide analysis of DGAT gene family in Perilla frutescens and functional characterization of PfDGAT2-2 and PfDGAT3-1 in Arabidopsis. (November 2022) - Xu, Huaxiang; Li, Dan; Hao, Youjin; Guo, Xi; Lu, Junxing; Zhang, Tao
Abstract: Diacylglycerol acyltransferase (DGAT) is the rate-limiting enzyme that catalyzes the final step in triacylglycerol biosynthesis, however, members of DGAT gene family of Perilla frutescens has not yet been identified and characterized. In this study, a total of 20 PfDGAT genes were identified from the genome of Perilla frutescens and were divided into four groups (PfDGAT1, PfDGAT2, PfDGAT3, PfWS/DGAT) according to their phylogenetic relationships. These were unevenly distributed across the 12 chromosomes. Sequence analysis revealed that PfDGAT members of the same subfamily have highly conserved gene structures, protein motifs and cis -acting elements in their promoters. Gene duplication analysis showed that random duplication and segmental duplication contributed to the expansion of the DGAT family in P. frutescens . RNA-seq and qRT-PCR analysis suggested that they may play a role in the growth and development of Perilla, especially in the accumulation of seed oil. Compared with the wild-type, seed length, width, and 1000-seed weight of transgenic PfDGAT2-2 and PfDGAT3-1 Arabidopsis were significantly increased, as well as the seed oil content increased by 7.36–15.83 %. Over-expression of PfDGAT2-2 could significantly increase the content of C18:3 and C20:1 in Arabidopsis, while over-expression of PfDGAT3-1 could significantly enhance the content of C18:2 and C18:3. In conclusion, in this study the characteristics and potential functions of the PfDGAT family members were elucidated. Our findings provided basic information for further functional studies and helped to increase the yield and quality of Perilla oil. Highlights: 20 PfDGAT genes were identified in P . frutescens genome. Expression levels of PfDGAT genes were significantly increased during the development of seed. Over-expression of PfDGAT2-2 or PfDGAT3-1 in Arabidopsis significantly increased oil content and changed the composition of fatty acids in seeds. PfDGAT2-2 and PfDGAT3-1 were highly correlated with the accumulation of α-linolenic acid.